The Blood Transfusion Outcomes and Analysis of Factors Associated with Blood Transfusion Reactions in Orthopaedic Trauma Patients Managed at Moi Teaching and Referral Hospital, Eldoret, Kenya - Ngetich, Kibiwot Geofrey; Ayumba, Barry R.; Lotodo, Cherop Teresa (British Journal of Healthcare and Medical Research, 2026)
Background: Blood transfusion is required in the management of life threatening orthopaedic trauma hemorrhage. However, it is necessary to categorize the patients on the need for blood transfusion as well as adhering to the blood transfusion guidelines in order to avoid risks and hence ameliorate challenges and have good outcomes. Objective: To establish the blood transfusion outcomes and analyze the factors associated with blood transfusion reactions in the orthopaedic trauma patients managed at Moi Teaching and Referral Hospital (MTRH), Eldoret, Kenya. Methods: A hospital based descriptive cross-sectional study of 132 transfused orthopedic trauma patients was carried out between March, 2019 and January, 2020 at MTRH, after approval by relevant authorities. The patients were recruited by consecutive sampling method. Data on blood transfusion outcomes, as well as on factors associated with blood transfusion reactions (Sociodemographic, trauma and laboratory characteristics) was collected using interviewer administered structured questionnaire. Analysis of the aforementioned factors using the Fisher’s Exact Test was done and p value < 0.05 was considered statistically significant. Results: A total of 15 out of 132 patients (11.4%) had minor blood transfusion reactions. No mortality was recorded. Majority (6) were young (age group 21- 30 years old), followed by age group 41- 50 years old (5). Male (10) dominated over female (ratio- 2:1). Majority (13) were victims of RTA, 8 had long bones fractures, and debridement done in 8 patients. Majority (12) had Haemoglobin level of 7.1- 10.0 g%, and blood groups A+ and O+ (5 each). The findings on analysis of association of blood transfusion reactions and the stated factors were all not statistically significant (p>0.05). Conclusion: The incidence of blood transfusion reactions was low (11.4%). Majority of patients were young with male dominance. Majority of patients were victims of RTA, with long bones fractures who were done debridement. Most were of moderate low haemoglobin level and of blood groups A and O positive. Recommendations: High index of suspicion is necessary for diagnosis of blood transfusion reactions and cautions to eradicate these reactions be put in place. Further study on healthcare providers’ knowledge on blood transfusion, and the pattern of reactions noted in this study need be encouraged.